The impact of anchor characteristics on consumers’ willingness to pay a premium for food—an empirical study - Maojie, Zhou (Frontiers in Nutrition, 2023)
In the food industry space, Netflix foods have exploded onto the Internet on the back of social media and many consumers are paying a premium for them. So what are the motives that may inspire consumers' willingness to pay premium? In this paper, from the perspective of anchor, an external cue, a questionnaire survey was conducted with 275 respondents and analyzed using SPSS software. The results show that anchor characteristics (interactivity, professionalism and popularity) can influence consumers' perceived value and increase their premium purchase intention. Perceived value mediates the relationship between anchor characteristics and willingness to pay a premium. Limited-time limited-quantity positively moderated the relationship between perceived value and premium purchase intention. The results reveal the key role of anchors in consumers' decision-making process of buying Netflix food at a premium, and provide a theoretical basis for enterprises to select and cultivate anchors for product promotion.